Microbial and enzymatic changes in natural soursop puree during storage - A., Umme; Y., Salmah; B., Jamilah; Asbi, B.A. (Elsevier Science, 1999)
Microbial and enzymatic comparisons were made on natural soursop puree stored at 15, 4 and -20°C without pasteurisation and with pasteurisation at 79°C for 69 s. Results showed that pasteurisation caused significant decrease in microbial count in soursop puree from 6.4x103 to 8.5x101 cfu per g. Generally, storage at -20°C exhibited greater stability of samples as compared to those kept at 4 and 15°C. In contrast to microbial reduction, pasteurisation caused significant increase in cloud from 0.318 to 0.529 and completely inactivated the pectinesterase enzyme. The puree packed into foils kept at 4°C exhibited decreased cloud loss as compared to others packed in cans and bottles kept at 15 and -20°C. No pectinesterase enzyme regeneration was observed for pasteurised puree in this study during 12 weeks of storage time.